2021
DOI: 10.1002/jrs.6148
|View full text |Cite
|
Sign up to set email alerts
|

Polarized and non‐polarized Raman spectroscopy of ZnO crystals: Method for determination of crystal growth and crystal plane orientation for nanomaterials

Abstract: Analysis and determination of crystal orientation and exposed surface facets remain a challenge in nanomaterial science. In this work, we show that polarized and non-polarized Raman spectroscopy can be useful tools to determine crystal plane orientation and conveniently be applied to spatial dimensions limited only by the diffraction limit of the excitation laser. The methodology is exemplified for wurtzite structured ZnO. Three different crystal facets, ( 0001), (1 1 00), and (11 2 0), of ZnO are investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The results indicate that both samples have almost the same fraction of polar planes, about 60%. 60 This interpretation confirmed that both samples have a similar crystal growth orientation, consistent with the XRD analysis.…”
Section: Resultssupporting
confidence: 83%
“…The results indicate that both samples have almost the same fraction of polar planes, about 60%. 60 This interpretation confirmed that both samples have a similar crystal growth orientation, consistent with the XRD analysis.…”
Section: Resultssupporting
confidence: 83%
“…As displayed in Figure a, the main diffraction peaks which locate at 31.7°, 34.4°, 36.2°, 47.5°, 56.5°, 62.8°, and 67.9° are corresponding to the hexagonal wurtzite structure of ZnO (JCPDS: 36‐1451). [ 12,20,21 ] However, compared with pure ZnO‐T, the peak intensity of the composite is obviously weaker. Meanwhile, the diffraction peak appeared at 28.6° can be assigned to ZnS (JPCDS: 65‐1691).…”
Section: Resultsmentioning
confidence: 99%
“…The Raman spectra of Cu 2 O, Cu 4 O 3 , CuO, and ZnO-Q-dot films are depicted in Figure B. The Raman spectroscopy measurements of the ZnO Q-dots show the position of the strongest Raman peaks (438 and 100 cm –1 ) and that the expected peaks at 333, 378, 411, and 438 cm –1 merge due to significant peak broadening, thus forming a broad absorption band between about 300 and the 438 cm –1 peak. Peak broadening in nanoparticles has previously been reported for Si and is attributed to thermal heating and size distribution of the nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Cu 2 O and Cu 4 O 3 are very sensitive to laser power density and are oxidized if too much laser power is used. , Therefore, a low laser power, 0.44 mW, at the sample was used for the measurements. Because of the orientation-dependent Raman scattering of ZnO, it is possible to investigate if the particles deposit in a preferred orientation using circularly polarized Raman spectra, according to the method recently published by our group . Large peak broadening, however, preventing the detailed analysis of the 378 cm –1 peak, complicated the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation